Comparative Analysis of Calcium Content in Milkfish by Varying of Wet and Dry Conditions Using AAS Instrumentation - Irman Idrus; Sabda Wahab; Faizal Mustapa; Dwiprayogo Wibowo (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
Standard method to determine some metal and metalloid elements using atomic absorption spectrometry (AAS) instrument has been widely applied based on the absorption of radiation by free atoms. Thus, this study applied the standard AAS method to determine calcium (Ca) levels by varying wet and dry milkfish (Chanos chanos) in order to observe high Ca content categorized for healthy food. The preparation of milkfish were done by varying the condition of wet and dry meat. Fish meat was washed, crushed, dried, and extracted then filtered to get the filtrate from milkfish. It was analyzed based on qualitative observation that the [(NH4)2CO3] and [(NH4)2C2O4] reagents have reacted with the Ca element to form precipitates as CaC2O3 and CaC2O4. Furthermore, quantitative data using the AAS instrument to observe the Ca content of wet and dry meat shows that the wet milkfish has Ca content at an average of 0.0152 mg.g-1, whereas in dry meat conditions it shows an increase in Ca level to 0.0192 mg.g-1. This work has provided an overview of dietary requirements for the determination of Ca content in milkfish under dried meat which is very suitable for developing healthy food.